Implementasi E-Government dalam Pelayanan Publik (Studi Kasus Penyelenggaraan Pelayanan KTP Elektronik di Kecamatan Pulomerak) - Ana Maria Sri Hariyati; Indah Nurayuni; Ismi Syarifatus Sa'diyah; Augustin Rina Herawati; Kismartini Kismartini (Jurnal Manajemen dan Ilmu Administrasi Publik (JMIAP), 2022)
The purpose of writing is to analyze the Implementation of E-Government in Public Services with a case study of the Implementation of Electronic ID Card Services in Pulomerak District. The indicators used are accountable, participatory, orderly, and precise. This study uses a qualitative method with data sources, namely secondary data with data collection techniques library research. The data analysis used in this research is descriptive analysis. The results of the study indicate that the application of the Electronic ID card in Pulomerak District cannot be said to be effective so that the output produced is not optimal and in accordance with the objectives of population administration. Despite the many obstacles and problems that occurred during the implementation of the Electronic ID card program, there has been positive progress in the administrative system. The local government needs to improve the quality of human resources, especially technical employees and increase the provision of infrastructure for printing electronic ID cards. It can be concluded that so far the implementation of electronic ID card services in Pulomerak District has not run optimally, but it has been able to bring changes in the form of reducing double data in Pulomerak District.